INFLUÊNCIA DO LASER DE BAIXA INTENSIDADE NA VELOCIDADE DA MOVIMENTAÇÃO ORTODÔNTICA - Sousa, Marinês Vieira da Silva (2008)
This study investigated the effects of low-intensity laser on the rate of orthodontic movement of canines submitted to initial retraction. The sample was composed of 26 maxillary and mandibular canines, submitted to initial retraction with Niti coils with an force of 150g. One canine was irradiated with diode laser according to the following protocol: 780nm/20mW/5Jcm2/0.2J per point/Et=2J, at 0, 3 and 7 days after activation; the contralateral tooth was used as placebo. Retraction was performed for 4 months in the average, adding up to 9 laser applications. Dental casts obtained at each month were digitized on a 3D Scanner (3Shape) and the three-dimensional images were analyzed on the software Geomagic Studio 5 to measure the quantity of movement of retracted canines. Statistical analysis was performed by three-way Analysis of Variance, followed by the Tukey test (p<0.05). For evaluation of tissue integrity, initial and final periapical radiographs of retracted canines and molars were obtained, to evaluate a possible alveolar crest resorption by assessment of the distance from the alveolar bone crest to the cementoenamel junction, as well as the level of root resorption by the Levander and Malmgreen index, which was evaluated only on retracted canines. The non-parametric Wilcoxon test was applied for that purpose (p<0.05). The results indicated a statistically significant increase in the rate of movement of irradiated canines compared to the contralateral teeth, at all periods, as well as maintenance of tissue integrity. Thus, it was concluded that the diode laser may accelerate the orthodontic movement, contributing to reduce the treatment time.(AU)